ANALISIS KEMANDIRIAN BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPA TERPADU DI SMP NEGERI 1 RAMBAH SAMO KABUPTEN ROKAN HULU TAHUN PEMBELAJARAN 2014/2015 - -, Mashur; Lestari, Rena; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The purpose of this study was to determine the independence of class VII student learning in science subjects Integrated in SMP Negeri 1 Rambah Samo Rokan Hulu academic Years 2014/2015. This study is descriptive qualitative. Samples of this research are students of class VII A and VII B of 60 students selected by random sampling. Technique collecting the data used questionnaires. After analyzing the data obtained by the average percentage of 69.34 % indicator. The results of the analysis, it can be concluded that the independence of class VII student learning in science subjects Integrated in SMP Negeri 1 Rambah Samo Rokan Hulu Year 2014/2015 Learning categorized quite good